Splendours of Mesopotamia - John Curtis; Michael Seymour; Nigel Tallis; Sarah Collins; Walid Yasin (TDIC, Abu Dhabi, 2011)
Exhibition of archaeological treasures of the ancient civilizations of the Mesopotamian region. Joint collaboration between the British Museum, Al Ain National Museum and TDIC, Abu Dhabi.
Also available in Arabic with the title: (3QhGFY HdGO GdQGaOjfs
English
Keywords: Ancient; N4390-5098 Exhibitions; Iraq